Politeness Strategies in Everyday English Discourse - Hafizov Abror Alisher ugli (Genius Journals, 2022)
Conversation strategies are an important element of any modern English language learning program. Business English classes place great emphasis on teaching these strategies. Politeness strategies are an important component of business conversation strategies. Understanding linguistic politeness as a strategy of speech behavior allows interlocutors to maintain a successful communication model and avoid conflicts. This study focuses on politeness strategies used in business English speech. As part of the study, a corpus of precedents was subjected to a comparative analysis, during which their general pragmatic effect on the interlocutor was determined. Emphasis has been placed on the statistical analysis of the distribution of four politeness strategies and their respective substrates in English-speaking business communication. The study includes comparative statistics showing the manifestation of various politeness strategies in modern business English and describes the most frequent cases of their implementation. Increasing awareness of politeness strategies and acquiring practical skills will help both the speaker and the listener to understand the meanings expressed in different communication situations and adapt speech behavior to achieve communication goals, which will ensure business success
Keywords: politeness theory; politeness strategies; business communication; conversational strategies